Response to H. Floris Cohen's essay review on Newtonian scholarship. Issue 2 (June 2019) - Stan, Marius
Abstract : In a review of recent Newton scholarship, H. Floris Cohen charges that my paper is not a 'case of worthwhile innovation, or even of any innovation at all'. I beg to differ.